Doyle, Nicole. Bell Island Ghost Story. - Jarvis, Dale Gilbert, 1971- (2011)
Recording of a ghost story told by Nicole Doyle, a Grade 9 student at St. Michael's Regional High. Recorded in the Newman Wine Vaults Provincial Historic Site as part of the Young Folklorists Program run by the Heritage Foundation of Newfoundland and Labrador in May, 2011. Nicole writes, "This story takes place on Bell Island, Newfoundland. It is a very snall island with very big mysteries. The island is a very woodsy area and it has been told that there are hags, fairies, witches and more in the woods. I never believed that i would be a victim of one of these ghostly encounters. Though, one night I wanted to walk home through the woods, and saw the scare of my life! I had witnesses, so I know that I wasn't just seeing things. I went back to make sure that it was not just an illusion. Well, it was definitely not an illusion!"